2022
DOI: 10.1111/sdi.13049
|View full text |Cite
|
Sign up to set email alerts
|

Antibody responses to inactivated SARS‐CoV‐2 vaccine in peritoneal dialysis patients

Abstract: Introduction As end‐stage renal disease (ESRD) patients generally have reduced responses to the vaccines, effectiveness of newly developed SARS‐CoV‐2 vaccines in ESRD are also matters of curiosity. We aimed to investigate the humoral responses of our peritoneal dialysis (PD) patients to the inactivated SARS‐CoV‐2 vaccine. Methods Humoral immune responses of 23 PD patients who received two doses of the inactivated SARS‐CoV‐2 vaccine were investigated with a commercial test that measures IgG antibodies towards r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…In HD patients, the weakening of innate and adaptive immune systems functions due to the decrease in both skewed Th1/Th2 T-cell ratios and dendritic and T-cell cells increase the tendency to infections. Therefore, it is important to determine the periodic intervals of additional doses by determining the antibody levels of these patients during the ongoing pandemic process [3,10,11].In recent studies in HD patients, the antibody level was 80% after two doses of SARS-CoV-2 inactivated vaccine, while the Serologic response in HD patients with mRNA vaccine was approximate90% [12,13] .These results are one month after the second dose of vaccine. Presumably, these levels may decrease as the antibody levels are checked again in the following weeks.…”
Section: Resultsmentioning
confidence: 99%
“…In HD patients, the weakening of innate and adaptive immune systems functions due to the decrease in both skewed Th1/Th2 T-cell ratios and dendritic and T-cell cells increase the tendency to infections. Therefore, it is important to determine the periodic intervals of additional doses by determining the antibody levels of these patients during the ongoing pandemic process [3,10,11].In recent studies in HD patients, the antibody level was 80% after two doses of SARS-CoV-2 inactivated vaccine, while the Serologic response in HD patients with mRNA vaccine was approximate90% [12,13] .These results are one month after the second dose of vaccine. Presumably, these levels may decrease as the antibody levels are checked again in the following weeks.…”
Section: Resultsmentioning
confidence: 99%
“…In a previous study, the initial seroconversion rate of PD patients with inactivated vaccine was not different from healthy controls [ 13 ]. However, in this comparison over 6 months of time without a booster dose, we found that maintenance of seropositivity was significantly lower in PD patients than healthy controls (44% vs. 88%).…”
Section: Discussion/conclusionmentioning
confidence: 97%
“…PD and HD patients might have different immune profiles. Some previous SARS-CoV-2 vaccine studies showed higher initial immunogenicity in PD patients [ 10 , 13 ]. However, with this study, we found similar antibody levels and seropositivity rates for PD and HD patients 6 months after initial vaccinations.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“… 1 , 2 Murt et al showed that 95.6% of PD patients developed SARS‐CoV‐2 IgG seropositivity 3–4 weeks following two doses of inactivated SARS‐CoV‐2 vaccine (CoronaVac, developed by Sinovac Life Sciences). 3 Sustained antibody responses 6 months following two doses of BNT162b2 were recently reported in a cohort of 64 PD patients. 4 A UK study involving hemodialysis patients showed differential early immune response to BNT162b2 and AZD1222 vaccines with the latter inducing suboptimal neutralizing antibody levels.…”
mentioning
confidence: 92%